The need of gamified assessment for engaging learning experience - Norhusyairi Hawari; Nurul Hidayah Mat Zain; Aslina Baharum (Bulletin of Electrical Engineering and Informatics, 2020)
Gamification described as the use of game elements for purposes beyond games. As an extension of that, gamified assessment is defined as the use of gamification for assessment purposes. However, the traditional method of assessment remains the standard for student performance assessment, and this raises two assumptions. First, the current gamification implementation is still in its infancy. Thus, it is still unappealing enough for practical use. Second, there is a lack of study that brings forward the desire to have gamification implemented in the assessment. Hence, this study intends to explore the student’s perception of gamified assessment followed by their verdict, acquire the strength and weakness points of the existing implementation. In total, 86 students across several universities in Malaysia involved in this study. The present study implemented standard descriptive statistical methods for analyzing the data. The findings showed that there are needs for gamified assessment for an engaging learning experience. Besides, the results showed one of the earlier presumptions, which is the lack of study that points toward the student’s desire to have a gamified assessment. Keenly, the results of the study will emphasize the need for developing a rigorous gamified assessment model as a guideline to develop an application that engaging learning experience.